La Cohésion Sociale En Côte d'Ivoire: Analyse De La Situation Et Facteurs Selon Les Ivoiriens - Sali Lokotianwa Yeo Kone (European Scientific Journal, ESJ, 2018)
This study proposes to examine the situation of social cohesion in Côte d'Ivoire. To do this a survey is conducted on a sample of 1536 Ivoirians in the four major regions of Côte d’Ivoire in both rural and urban areas. This sample is composed of 60 ethnic groups grouped into four (04) groups. The size of the sample obtained by the quota method (region, sex, agglomeration, age (18 years and over) socio-professional situation) is calculated taking into account the data of the last General Census of Population and Housing (RGPH., 2014). The results reveal that the Ivorian aware of his role also relies on public authorities to reduce disparities and polarizations. This will give people the impression that they are involved in a common enterprise, that they face the same challenges and are part of the same community.